Development and evaluation of a laboratory module on the topic "water retention in toads" for college biology students - Abaygar, Irene Flores 1950- (1978)
The study involved the development, try-out and expansion of a teaching module designed as a laboratory exercise for first year college students on the topic: Water Retention in Toads. Development of the module was patterned after the module format design of Dr. Jabe Kahle. A modular material was created consisting of a 20-item diagnostic pre-test, a 31-page study guide and a 20-item post-test. Evaluation in the form of Consultant/peer evaluation, self-evaluation and student-user evaluation showed that the modular material was well-constructed and developed cognitive knowledge, comprehension, application, analysis and processes of scientific inquiry I and III skills, all related to osmoregulation in toads.
"July, 1978."
Vita.
Thesis (M. A.T. : Biology)--University of the Philippines, Diliman.
Keywords: Biology -- Philippines -- Laboratory manuals; Biology -- Study and teaching (Higher) -- Philippines -- Iloilo; Toads as laboratory animals